Principles for Modeling Dose-Response for the Risk Assessment of Chemicals. - Organization, World Health (Environmental Health Criteria Series, No. 239., 2009)
This volume is part of the ongoing review of the underlying scientific bases for decision-making in chemical risk assessment by International Programme on Chemical Safety. It involves specific consideration of the area of dose-response assessment in the evaluation of information from toxicological studies in animals and from human clinical and epidemiological studies. It covers toxicants with threshold effects and those for which there may be no practical threshold, such as substances that are genotoxic and carcinogenic. The discussions are concerned with that subset of cause-effect relationsh.